2018
DOI: 10.1080/17501229.2018.1418633
|View full text |Cite
|
Sign up to set email alerts
|

Researching mobile-assisted Chinese-character learning strategies among adult distance learners

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…With the implementation of technologies in CFL teaching, however, recent studies reveal that students largely utilised technologies to facilitate their character learning (e.g., Kuo & Hooper, 2004;X. Liu & Olmanson, 2016;Qian, Owen, & Bax, 2018;Mason & Zhang, 2017). The latest research shows that radical knowledge, typing, and playing games, with the aid of a variety of online platforms and mobile applications, can accelerate character acquisition and enhance learning outcomes.…”
Section: L2 Learners' Strategies For Learning Chinese Charactersmentioning
confidence: 99%
See 1 more Smart Citation
“…With the implementation of technologies in CFL teaching, however, recent studies reveal that students largely utilised technologies to facilitate their character learning (e.g., Kuo & Hooper, 2004;X. Liu & Olmanson, 2016;Qian, Owen, & Bax, 2018;Mason & Zhang, 2017). The latest research shows that radical knowledge, typing, and playing games, with the aid of a variety of online platforms and mobile applications, can accelerate character acquisition and enhance learning outcomes.…”
Section: L2 Learners' Strategies For Learning Chinese Charactersmentioning
confidence: 99%
“…Pleco was the most frequently used mobile app. Qian, Owen, & Bax (2018) found that UK-based distance learners at the beginner Chinese level adopted some new strategies to learn characters, such as typing pinyin to learn to recognise new characters and constant self-testing. Notwithstanding the proven effectiveness of technology-supported strategies in current character learning, no study has examined CFL learners' strategies for learning characters in emergency online teaching.…”
Section: L2 Learners' Strategies For Learning Chinese Charactersmentioning
confidence: 99%
“…Irish CFL learners frequently exercised cognitive strategies (Bruen, 2020), while Spanish CFL learners did not deploy these strategies that much (Wang and Cáceres-Lorenzo, 2019). In addition, it has been reported that affective strategies were favored by the British CFL learners (Qian et al, 2018), but least frequently deployed by their Australian counterparts (Jiang and Wu, 2016).…”
Section: Strategy Use In Chinese Language Learningmentioning
confidence: 99%
“…Previous research on the use of technologies for language teaching and learning has focused on issues such as usability (see, e.g., Stevenson and Liu 2010), effectiveness (see, e.g., Macaro et al 2012), or how digital technologies have been changing learners' learning strategies (see, e.g., Qian et al 2018). For instance, Stevenson and Liu (2010) focused on exploring the pedagogical usability of three online language learning sites, aimed at finding out "how learnable and usable the website is for learners" (p. 235); Macaro et al (2012) offered a systematic review of 47 studies related to language teaching technologies and attempted to determine whether there are any direct benefits of using technologies for language education; Qian et al (2018) identified emerging Chinese learning strategies which were made prominent with the use of mobile technologies. Nevertheless, only limited research focuses on the design of materials with a multimodal perspective which brings to the fore the fact that, in addition to language, there are other kinds of resources that content creators use to facilitate (language) learning.…”
Section: The Design Of Multimodal Learning Environmentsmentioning
confidence: 99%